2008
DOI: 10.1113/jphysiol.2007.149500
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of large conductance, Ca2+‐activated K+ (BK) channels by α5β1 integrin activation in arteriolar smooth muscle

Abstract: Injury/degradation of the extracellular matrix (ECM) is associated with vascular wall remodelling and impaired reactivity, a process in which altered ECM-integrin interactions play key roles. Previously, we found that peptides containing the RGD integrin-binding sequence produce sustained vasodilatation of rat skeletal muscle arterioles. Here, we tested the hypothesis that RGD ligands work through α5β1 integrin to modulate the activity of large conductance, Ca 2+ -activated K + (BK) channels in arteriolar smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…The presence of the ␤1 BK channel subunit may also alter the functional effect of c-src-mediated BK channel phosphorylation (36). Although we expressed only the BK channel ␣-subunit in this study, we found similar degrees of mSlo current potentiation and integrin-induced increased Ca 2ϩ sensitivity with or without co-expression of the ␤1 BK channel subunit (15); however, we did not test the role of c-src under those conditions.…”
Section: Discussionmentioning
confidence: 40%
See 4 more Smart Citations
“…The presence of the ␤1 BK channel subunit may also alter the functional effect of c-src-mediated BK channel phosphorylation (36). Although we expressed only the BK channel ␣-subunit in this study, we found similar degrees of mSlo current potentiation and integrin-induced increased Ca 2ϩ sensitivity with or without co-expression of the ␤1 BK channel subunit (15); however, we did not test the role of c-src under those conditions.…”
Section: Discussionmentioning
confidence: 40%
“…␣5␤1 Integrin Activation Enhances BK Current-The activation of ␣5␤1 integrin by multivalent ligands such as FN or insoluble ␣5␤1 integrin antibody is associated with 30 -50% enhancement in whole-cell BK current in VSM cells (15). BK current enhancement could be reproduced with heterologously expressed mSlo channels ( Fig.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations